Inhibition of PLK1 by capped‐dose volasertib exerts substantial efficacy in MDS and sAML while sparing healthy haematopoiesis. (8th December 2019) - Dill, Veronika; Kauschinger, Johanna; Hauch, Richard T.; Buschhorn, Lars; Odinius, Timo O.; Müller‐Thomas, Catharina; Mishra, Ritu; Kyncl, Michele C.; Schmidt, Burkhard; Prodinger, Peter M.; Hempel, Dirk; Bellos, Frauke; et al.
Abstract: Introduction: Targeting the cell cycle machinery represents a rational therapeutic approach in myelodysplastic syndromes (MDS) and secondary acute myeloid leukemia (sAML). Despite substantial response rates, clinical use of the PLK inhibitor volasertib has been hampered by elevated side effects such as neutropenia and infections. Objectives: The primary objective was to analyse whether a reduced dose of volasertib was able to limit toxic effects on the healthy haematopoiesis while retaining its therapeutic effect. Methods: Bone marrow mononuclear cells (BMMNCs) of patients with MDS/sAML (n = 73) and healthy controls (n = 28) were treated with volasertib (1 μM to 1 nM) or vehicle control. Short‐term viability analysis was performed by flow cytometry after 72 hours. For long‐term viability analysis, colony‐forming capacity was assessed after 14 days. Protein expression of RIPK3 and MCL‐1 was quantified via flow cytometry. Results: Reduced dose levels of volasertib retained high cell death‐inducing efficacy in primary human stem and progenitor cells of MDS/sAML patients without affecting healthy haematopoiesis in vitro. Interestingly, volasertib reduced colony‐forming capacity and cell survival independent of clinical stage or mutational status. Conclusions: Volasertib offers a promising therapeutic approach in patients with adverse prognostic profile. RIPK3 and MCL‐1 might be potential biomarkers for sensitivity to volasertib treatment.